Information seeking behaviour of journalists in gathering, selecting and processing news pictures - Idris Rashid Khan Surattee (2009)
This study examined the information seeking behaviour of journalists in handling news pictures. This study was carried out in the context of journalists' actual working assignments in gathering, selecting and processing pictures for news stories. The survey of literature in the information needs and use studies helps identify dominant ideas and research trends in this field. This also helps to identify gaps in research some of which this study attempts to fill. The News Desk and Picture Desk of the Straits Times newspaper have established systematic procedures and techniques in gathering visual information for its news stories. Journalists including photo-journalists, functioning within this systematic set up, exhibited certain information seeking behavior patterns which are closely tied to their task environment. The criteria and considerations for selection of pictures used by journalists are explored. This study draws on conceptual framework and methodology from sociological studies. The qualitative phenomenological approach and concepts commonly used by research in the ethnomethodological school in sociology were adopted. The findings of this study are analysed and compared with the mainstream thinking on the subject. This reveals several points of departure particularly in terms of the impact of the social context on the information seeking behaviour process. This study therefore opens up new avenues for research into the complexity of journalists' information needs.